2013
DOI: 10.1109/jtehm.2013.2285916
|View full text |Cite
|
Sign up to set email alerts
|

Novel Flurometric Tool to Assess Mitochondrial Redox State of Isolated Perfused Rat Lungs After Exposure to Hyperoxia

Abstract: Recently we demonstrated the utility of optical fluorometry to detect a change in the redox status of mitochondrial autofluorescent coenzymes NADH (Nicotinamide Adenine Dinucleotide) and FAD (oxidized form of Flavin Adenine Dinucleotide (FADH2,)) as a measure of mitochondrial function in isolated perfused rat lungs (IPL). The objective of this study was to utilize optical fluorometry to evaluate the effect of rat exposure to hyperoxia (>95% O2 for 48 hours) on lung tissue mitochondrial redox status of NADH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…Table 7 shows that rat exposure to hyperoxia for 48 hrs increased FWHM time by ~50%. This suggests that ΔΨ m recovery from ADP-induced depolarization in mitochondria from hyperoxia lungs was substantially slower than that in normoxia lungs, consistent with decreases in complex I and II activities in lungs of hyperoxia rats (22). Table 7 shows that the ΔΨ m recovery time (FWHM) from ADP-stimulated depolarization, which increased with hyperoxia, partially reversed with hyperoxia+H 2 , consistent with the ability of H 2 to protect mitochondria from functional degradation by hyperoxia-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Table 7 shows that rat exposure to hyperoxia for 48 hrs increased FWHM time by ~50%. This suggests that ΔΨ m recovery from ADP-induced depolarization in mitochondria from hyperoxia lungs was substantially slower than that in normoxia lungs, consistent with decreases in complex I and II activities in lungs of hyperoxia rats (22). Table 7 shows that the ΔΨ m recovery time (FWHM) from ADP-stimulated depolarization, which increased with hyperoxia, partially reversed with hyperoxia+H 2 , consistent with the ability of H 2 to protect mitochondria from functional degradation by hyperoxia-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 62%
“…We previously demonstrated significant decreases in complex I and II activities in lung of rats exposed to hyperoxia for 48 hrs (22). Mitochondrial DNA (mtDNA) is highly sensitive to reactive oxygen species (ROS) (29).…”
Section: Discussionmentioning
confidence: 99%
“…This component of the enhanced HMPAO uptake could be due to the increased capillary endothelial permeability as measured by pulmonary endothelial filtration coefficient ( K f ) (Table 3) or altered mitochondrial redox state. Previously, we demonstrated that rat exposure to > 95% O 2 for 48 hrs decreased lung tissue mitochondrial complex I and II activities and altered mitochondrial redox state (32). …”
Section: Discussionmentioning
confidence: 98%
“… 67 70 PCP dissipates the proton gradient by consuming the proton motive force via increased proton leak back into the matrix. A recent study reported that PCP oxidizes the ETC and increase the activity of complex I, 71 leading to the production of more protons and transfer of more electrons along the ETC. Lack of proton gradient for phosphorylation and polarized ΔΨm, activates a mechanism to compensate for the uncoupling effect of PCP, by increasing proton pumping and respiration, in an attempt to reestablish the proton gradient.…”
Section: Discussionmentioning
confidence: 99%